Arctic Wool: Perspectives on Sustainable Craft Practices - Hernandez Cervantes, Fabiola (Research in Arts and Education, 2023)
This research presents the work of two women, a crafter and a farmer, and considers connections between people working with textiles, sustainable processes, local economy, traditional knowledge, and roles within the craft sector in the Finnish Arctic and Circumpolar region. Two qualitative interviews were conducted in Finland: one with a textile-dyeing artisan using sustainable processes and another with a farmer and yarn crafter. Crafters and farmers preserve heritage skills in the textile field, valuable to the continuation of traditional knowledge. Their network has an environmental impact on the craft sector, helping to preserve endemic breeds of sheep.